2006
DOI: 10.1074/jbc.m603133200
|View full text |Cite
|
Sign up to set email alerts
|

IKK-i/IKKϵ Controls Constitutive, Cancer Cell-associated NF-κB Activity via Regulation of Ser-536 p65/RelA Phosphorylation

Abstract: The transcription factor nuclear factor-B (NF-B) 2 plays a pivotal role in controlling the expression of a diverse set of genes that contribute to a variety of biological functions, including cell survival, cell proliferation, and immune and inflammatory responses (1). The classic form of NF-B is composed of a heterodimer of the p50 and p65 subunits, which is preferentially localized in the cytoplasm as an inactive complex with inhibitor proteins of the IB family. Following exposure of cells to a variety of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
131
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(145 citation statements)
references
References 39 publications
11
131
1
2
Order By: Relevance
“…Because we found that EGF-induced NF-kB activation in HEK293T cells is inhibited by expression of a dominant-negative IKKb mutant, we analysed the effect of EGF on p65 Ser-536 phosphorylation. Consistent with previously reported data (Adli and Baldwin, 2006), nuclear p65 was already significantly phosphorylated in untreated HEK293T cells. However, EGF did not further increase p65 Ser-536 phosphorylation.…”
Section: Discussionsupporting
confidence: 82%
“…Because we found that EGF-induced NF-kB activation in HEK293T cells is inhibited by expression of a dominant-negative IKKb mutant, we analysed the effect of EGF on p65 Ser-536 phosphorylation. Consistent with previously reported data (Adli and Baldwin, 2006), nuclear p65 was already significantly phosphorylated in untreated HEK293T cells. However, EGF did not further increase p65 Ser-536 phosphorylation.…”
Section: Discussionsupporting
confidence: 82%
“…However, the role for TANK in the IKK-dependent NF-kB signaling cascades remains controversial because TANK-depleted, knockdown cells do not show any defect in TNF-a-or LPSmediated IKK activation [21,58]. Nevertheless, these observations do not rule out the possibility that TANK might connect upstream kinases such as TBK1 and IKK-e, thereby promoting IKK-independent phosphorylation of the NF-kB proteins p65 [59,60], c-Rel [61] or p52 [62] in response to as yet poorly characterized signals. TANK constitutively binds to IKK-e [63] and TBK1 [64] through its N-terminal domain; this interaction is probably essential for the positive regulation of signal transduction by TANK because recent studies demonstrated that TANK is involved in some TLR-dependent IRF-activating pathways by promoting TBK1 and IKK-e-mediated phosphorylation of IRF3 and IRF7 [20,21].…”
Section: Reviewmentioning
confidence: 60%
“…In addition p65 Ser536 is the target of many kinases. There were multiple p65 Ser536 kinases have been described including IKKβ, RSK1, IKKα, IKKε and NAK [46][47][48][49]. But none of them was systematically studied in prostate system especially in T/E fusion expressing PCa.…”
Section: Discussionmentioning
confidence: 99%